2022
DOI: 10.3389/fpsyg.2022.829333
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Aspects of Teachers Regarding Working Behavior and Early Retirement

Abstract: Worldwide, a significant proportion of teachers retires prematurely for health reasons or at their own request. The study examines whether male and female teachers differ in terms of working conditions and coping with high work demands as well as individual factors that promote early retirement. A cross-sectional study was conducted to collect data from 6,109 full-time teachers in high schools (56% women). Weekly working hours from a four-week working time record and psychosocial work stress (effort-reward mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 110 publications
3
7
0
Order By: Relevance
“…Klassen and Chiu [ 68 ] studied 1,430 in-service teachers in western Canada and revealed that female teachers reported more workload- and classroom-related stress than male teachers. Similarly, other studies have suggested that females perceive slightly higher levels of stress than males in school settings [ 69 , 70 ]. Moreover, at the general population level, females were more often associated with higher stress levels than males during the first period of the COVID-19 pandemic [ 71 ].…”
Section: Discussionmentioning
confidence: 57%
“…Klassen and Chiu [ 68 ] studied 1,430 in-service teachers in western Canada and revealed that female teachers reported more workload- and classroom-related stress than male teachers. Similarly, other studies have suggested that females perceive slightly higher levels of stress than males in school settings [ 69 , 70 ]. Moreover, at the general population level, females were more often associated with higher stress levels than males during the first period of the COVID-19 pandemic [ 71 ].…”
Section: Discussionmentioning
confidence: 57%
“…A recent systematic review found overcommitment linked to impaired self-reported (e.g., fatigue, insomnia) and physiological health outcomes (e.g., blood pressure, atherogenic lipids) [ 26 ]. Moreover, overcommitment is positively linked to indicators of impaired energetic well-being, such as fatigue [ 27 ], burnout [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], emotional exhaustion [ 15 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], vital exhaustion [ 43 , 44 ], and need for recovery [ 27 , 45 ]. Other systematic reviews [ 26 , 46 ] found that overcommitment was associated with higher levels of (psycho)somatic complaints, also supported by more recent research [ 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to our literature research (see Supplementary Materials ), empirical evidence linking overcommitment to work-related rumination is almost non-existent. Among the studies identified, not all reported correlations between overcommitment and the other facets of work-related rumination were considered [ 31 , 41 , 67 ], leaving us with a very small set of studies.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review of ERI found that overcommitment is linked to impaired self-reported (e.g., fatigue, insomnia) and physiological health outcomes (e.g., blood pressure, atherogenic lipids) [25]. More specifically, there is empirical evidence that overcommitment is positively linked to indicators of impaired energetic well-being, such as fatigue [26], burnout [27][28][29][30][31][32][33][34], emotional exhaustion [15,[35][36][37][38][39][40][41], vital exhaustion (a compound of strain indicators including exhaustion) [42,43], and need for recovery [26,44]. Systematic reviews of ERI [45] and more specifically of overcommitment [25] found that overcommitment is associated with higher levels of (psycho)somatic complaints.…”
Section: Overcommitmentmentioning
confidence: 99%
“…In other words, empirical evidence linking overcommitment to work-related rumination is almost non-existent. Among the studies identified not all reported correlations between overcommitment and the facets of work-related rumination considered [30,40,65], leaving us with a very small set of studies. Below, we summarize and review the empirical evidence available.…”
Section: Links Between Overcommitment and Other Facets Of Work-relate...mentioning
confidence: 99%